Restorative proctocolectomy for familial adenomatous polyposis coexisting with colorectal cancer - Cüneyt KAYAALP; Sevil IŞIK; Soner AKBABA; Gürel NEŞŞAR; Erkan OYMACI; Canbek SEVEN (Turkish Journal of Gastroenterology, 2019)
-